Facets of Freedom: Social Death and Karmic Rebirth in Amitav Ghosh’s Sea of Poppies - Sneharika Roy (Universitat Autònoma de Barcelona, 2017)
This paper argues that Amitav Ghosh’s Sea of Poppies highlights the transcultural continuities between indenture in the Indian Ocean and the Atlantic slave trade, while simultaneously foregrounding the specificities of servitude in the Indian Ocean World. To do so, it demonstrates the remarkable relevance of Orlando Patterson’s concept of slavery as “social death” to the Indian experience of crossing of the “Black Water,” one that has traditionally been articulated through the cultural trope of death. However, rather than a simple reconfirmation of indentured labour as social death, Ghosh’s novel offers a nuanced, counter-balancing correlative to social death: karmic rebirth as narrative event and metaphoric idiom. By using the double-level of meaning offered by symbolism and allegory, Ghosh is able to sensitively balance exploitation and oppression on the one hand (the “outward” or objective reality of social death) and resistance and agency on the other (the “inward reality” of karmic rebirth). In this sense, his novel is ultimately a reaffirmation of Patterson’s Hegelian insight that slavery is not antithetical to freedom, but is the pre-condition for its emergence.